2019
DOI: 10.1590/0100-3984.2018.0123
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular invasion in hepatocellular carcinoma: is it predictable with quantitative computed tomography parameters?

Abstract: Objective To investigate whether quantitative computed tomography (CT) measurements can predict microvascular invasion (MVI) in hepatocellular carcinoma (HCC).Materials and Methods This was a retrospective analysis of 200 cases of surgically proven HCCs in 125 consecutive patients evaluated between March 2010 and November 2017. We quantitatively measured regions of interest in lesions and adjacent areas of the liver on unenhanced CT scans, as well as in the arterial, portal venous, and equilibrium phases on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Evaluation of the liver by imaging methods has been the subject of various recent studies in the radiology literature of Brazil (28)(29)(30)(31)(32) . The availability of affordable, good quality ultrasound machines has allowed the development of focused point-of-care ultrasound protocols applicable to tropical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the liver by imaging methods has been the subject of various recent studies in the radiology literature of Brazil (28)(29)(30)(31)(32) . The availability of affordable, good quality ultrasound machines has allowed the development of focused point-of-care ultrasound protocols applicable to tropical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the radiology literature of Brazil have emphasized the importance of imaging examinations in the evaluation of hepatic neoplasms (18)(19)(20)(21)(22)(23) . The present study used the LI-RADS classification system to analyze 38 patients infected with hepatitis viruses (HBV, HCV, HDV, or combinations thereof) who underwent CT. We found that approximately 32% of the patients presented with LI-RADS 5 observations (i.e., lesions diagnosed by imaging as classic HCC).…”
Section: Discussionmentioning
confidence: 99%
“…Classifier chains [11], [12] is one of the standard MLL methods, in which, conditional dependence between a label and its predecessors is modeled. Other approaches like As a demonstration, the relative locations of different gene types on the left-most chromosome may not be in the exact order on DNA string, or can even be on different chromosomes [6].…”
Section: Related Workmentioning
confidence: 99%
“…The transformation from HCC gene types diagnosis program to machine classification. As a demonstration, the relative locations of different gene types on the left-most chromosome may not be in the exact order on DNA string, or can even be on different chromosomes[6].…”
mentioning
confidence: 99%